The complexity of neutrophils in health and disease: Focus on cancer. (April 2020) - Carnevale, Silvia; Ghasemi, Somayehsadat; Rigatelli, Anna; Jaillon, Sebastien
Abstract: Neutrophils are essential soldiers of the immune response and their role have long been restricted to their activities in defence against microbial infections and during the acute phase of the inflammatory response. However, increasing number of investigations showed that neutrophils are endowed with plasticity and can participate in the orchestration of both innate and adaptive immune responses. Neutrophils have an impact on a broad range of disorders, including infections, chronic inflammations, and cancer. Neutrophils are present in the tumour microenvironment and have been reported to mediate both pro-tumour and anti-tumour responses. Neutrophils can contribute to genetic instability, tumour cell proliferation, angiogenesis and suppression of the anti-tumour immune response. In contrast, neutrophils are reported to mediate anti-tumour resistance by direct killing of tumour cells or by engaging cooperative interactions with other immune cells. Here we discuss the current understandings of neutrophils biology and functions in health and diseases, with a specific focus on their role in cancer biology and their prognostic significance in human cancer.